2007
DOI: 10.1074/jbc.m702267200
|View full text |Cite
|
Sign up to set email alerts
|

Selenoprotein H Is a Redox-sensing High Mobility Group Family DNA-binding Protein That Up-regulates Genes Involved in Glutathione Synthesis and Phase II Detoxification

Abstract: Selenoprotein H is a recently identified member of the selenoprotein family whose function is not fully known. Previous studies from our laboratory and others showed that Drosophila melanogaster selenoprotein H is essential for viability and antioxidant defense. In this study we investigated the function of human selenoprotein H in murine hippocampal HT22 cells engineered to stably overexpress the protein. After treatment of cells with L-buthionine-(S,R)-sulfoximine to deplete glutathione, selenoprotein H-over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 21 publications
(19 reference statements)
2
84
0
Order By: Relevance
“…SelH-deficient cells display persistent DNA damage, increased oxidative stress and Nrf2 activation, and decreased GSH level. Previous reports suggest dual roles of human SelH as an oxidoreductase and a transactivator on genes involved in GSH synthesis and phase II detoxification (24,27). Although these results are based on overexpressed SelH in immortalized mouse cells incapable of developing replicative senescence, they offer insightful clues to explain the new role of SelH demonstrated herein.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…SelH-deficient cells display persistent DNA damage, increased oxidative stress and Nrf2 activation, and decreased GSH level. Previous reports suggest dual roles of human SelH as an oxidoreductase and a transactivator on genes involved in GSH synthesis and phase II detoxification (24,27). Although these results are based on overexpressed SelH in immortalized mouse cells incapable of developing replicative senescence, they offer insightful clues to explain the new role of SelH demonstrated herein.…”
Section: Discussionmentioning
confidence: 55%
“…The expression of glutamylcysteine synthetase, a key enzyme for de novo GSH biosynthesis, is increased in murine hippocampal HT22 cells overexpressing human SelH (27). Here we showed that the level of intracellular GSH was significantly lower (p Ͻ 0.05) in SelH shRNA than in scrambled shRNA HeLa cells before and after exposure with H 2 O 2 for 24 h (Fig.…”
Section: Gsh Deficiency and Nuclear Pnrf2 Accumulation In The Apoptotmentioning
confidence: 55%
“…108 It is moderately expressed in various mouse tissues, whereas elevated expression levels were found in brain during early development, but also in the thyroid, lung, stomach, and liver human tumors. 109 These data suggest a possible role of SelH in cellular proliferation during development or cancer growth.…”
Section: Selenoprotein Hmentioning
confidence: 99%
“…SelH is also involved in up-regulating the levels of GSH, the activity of GPx and the total antioxidant capacity in response to the redox state, with protective effects against superoxide and cell damage induced by ultraviolet B (UVB) irradiation. 108,110 A recent study has shown that SelH may exert its protective function through the activation of mitochondrial biogenesis signalling pathway by increasing the level of the nuclear encoded regulators PGC-1a, NRF1 and Tfam. 111 …”
Section: Selenoprotein Hmentioning
confidence: 99%
“…There are, in fact, five human GPX selenoenzymes: GPX1-4 and 6. In addition to the GPX enzymes, other selenoproteins to which antioxidant or redox properties have been attributed include thioredoxin reductase-1, -2 and -3 as well as selenoproteins H, P, R and W (12)(13)(14)(15). A total of 25 selenoproteins have been identified in humans, 24 of which exist as selenoproteins in rodents (16).…”
mentioning
confidence: 99%